Particulate matter, PM 10 & PM 2.5 levels, and airborne mutagenicity in Chiang Mai, Thailand - Vinitketkumnuen U. (2014)
Daily levels of particulate matter (PM) in the ambient air (PM 2.5 and PM 10) were measured in a northern city of Thailand (Chiang Mai) from March 1998 to October 1999. Twenty-four-hour air particulate matter samples were collected each day with Airmetric Minivol portable air samplers. Monthly averages of PM 2.5 from four stations in Chiang Mai varied from 15.39 to 138.31μg/m3 and 27.29 to 173.40μg/m3 for PM 10. The PM 2.5 annual average was 58.48mg/m3 and PM 10, 86.38μg/m3. Daily PM 2.5 (24h values) during the winter months in Chiang Mai frequently exceeded 200-300μg/m3. The maximum concentrations of PM 2.5 (24h average) in Chiang Mai air from December 1998 to April 1999 were 2.8-, 3.5-, 4.2-, 6.5- and 3.2-fold higher than the US Environmental Protection Agency (US EPA), PM 2.5, 24h standard of 65μg/m3. From May to October, the mean 24h levels of PM 2.5 and PM 10 were at acceptable levels. The data shows that during the winter season (December to March), levels of PM 2.5 and PM 10 in the Chiang Mai atmosphere are very high, and there may be significant health implications associated with these high concentrations. During the summer season, the fine particles were generally within the acceptable levels. To our knowledge, these are the first measurements of PM 2.5 to be reported for the city of Chiang Mai and they indicate considerable ambient fine particle exposures to the Chiang Mai population. In addition, dichloromethane extracts of airborne particulate matter PM 2.5 or PM 10 collected in the months of winter in the city of Chiang Mai were mutagenic to Salmonella typhimurium strain TA100 without metabolic activation. The mutagenicity appeared to track particle concentrations and increased in the presence of S9 mix. © 2002 Elsevier Science B.V. All rights reserved.